Review of Constructivism Theory In Analyzing Conventional Learning Media for Arabic Subjects - Salma Salsabila Prissa; Maman Abdurahman; Shofa Musthofa Khalid (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study explores the use of conventional teaching media in Arabic language instruction at a Madrasah Ibtidaiyah in Kuningan, using constructivist theory as an analytical framework. Employing a qualitative case study approach, data were collected through classroom observations and interviews with teachers and students, then analyzed using the Miles and Huberman model. Findings show that while blackboards and textbooks align with students’ cognitive development, their use does not fully support active, collaborative, or reflective learning. Lower-grade students remain teacher-dependent, whereas upper-grade students begin to show autonomy, though collaborative interaction is still minimal. This research highlights the untapped potential of conventional media in resource-limited settings and contributes to the theoretical discourse on constructivism by emphasizing the need for more participatory and contextual learning strategies. It calls for teachers to redesign instruction that integrates constructivist principles with available media to foster deeper student engagement. Future studies should compare conventional and digital media across diverse contexts to further enrich the pedagogical application of constructivist theory in language learning.   Abstrak Penelitian ini mengeksplorasi penggunaan media pengajaran konvensional dalam pembelajaran bahasa Arab di Madrasah Ibtidaiyah di Kuningan, dengan menggunakan teori konstruktivis sebagai kerangka analisis. Dengan menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui observasi kelas dan wawancara dengan guru dan siswa, kemudian dianalisis menggunakan model Miles dan Huberman. Temuan menunjukkan bahwa meskipun papan tulis dan buku teks selaras dengan perkembangan kognitif siswa, penggunaannya tidak sepenuhnya mendukung pembelajaran aktif, kolaboratif, atau reflektif. Siswa kelas bawah masih bergantung pada guru, sementara siswa kelas atas mulai menunjukkan otonomi, meskipun interaksi kolaboratif masih minim. Penelitian ini menyoroti potensi media konvensional yang belum dimanfaatkan dalam lingkungan terbatas sumber daya dan berkontribusi pada wacana teoretis tentang konstruktivisme dengan menekankan perlunya strategi pembelajaran yang lebih partisipatif dan kontekstual. Penelitian ini mendorong guru untuk mendesain ulang pembelajaran yang mengintegrasikan prinsip-prinsip konstruktivis dengan media yang tersedia guna mendorong keterlibatan siswa yang lebih mendalam. Penelitian selanjutnya sebaiknya membandingkan media konvensional dan digital dalam berbagai konteks untuk lebih memperkaya penerapan pedagogis teori konstruktivis dalam pembelajaran bahasa.